Incidence and Risk Factors for Developing Post-Traumatic Hydrocephalus, Analysis of a Prospective Cohort of 402 Patients. (1st September 2019) - Goldschmidt, Ezequiel; Angriman, Federico; Jha, Ruchira Menka; Zusman, Benjamin; Puccio, Ava; Okonkwo, David O
Abstract: INTRODUCTION: Post-traumatic hydrocephalus (PTH) is a common complication after traumatic brain injury (TBI). PTH incidence and risk factors have principally been derived from retrospective studies or those in the context of hydrocephalus following decompressive craniectomy. The goal of this study was to identify, in a large prospective cohort, the incidence and risk factors for PTH. METHODS: This is a single-center retrospective review of a prospectively collected database of patients with severe TBI. PTH was defined as the need for permanent CSF diversion by shunt insertion. Patient demographics, GCS, bleeding patterns, intracranial pressure (ICP) monitoring, and the need for a decompressive craniectomy were considered as explanatory variables. An inverse probability weighted logistic regression model, which considers potential censoring induced by in-hospital mortality, was used as our primary analysis. RESULTS: Of the 402 patients included, 40 required permanent CSF for a PTH cumulative incidence of 10% (95% CI: 7.3-13.6). PTH was associated with the need for a decompressive craniectomy [odds ratio (OR): 3.62 (1.62-8.07), P < .01]. Neither age nor gender nor GCS nor bleeding pattern (including intraventricular hemorrhage) was associated with the occurrence of PTH. There were no differences on the initial ICP measurement (10.1 (8.8) vs 9.9 (7.9) mm Hg) or the trend of the ICP between patients who ultimately developed PTH and those who did not. CONCLUSION: PTH develops in approximately 10% of patients with severe TBI. Patients who require a decompressive craniectomy are at a higher risk. Neither intracranial hypertension nor intraventricular hemorrhage was a relevant risk factor.